2016
DOI: 10.1016/j.scijus.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The non-contact detection and identification of blood stained fingerprints using visible wavelength reflectance hyperspectral imaging: Part 1

Abstract: Blood is one of the most commonly encountered types of biological evidence found at scenes of violent crime and one of the most commonly observed fingerprint contaminants. Current visualisation methods rely on presumptive tests or chemical enhancement methods. Although these can successfully visualise ridge detail, they are destructive, do not confirm the presence of blood and can have a negative impact on DNA sampling. A novel application of visible wavelength reflectance hyperspectral imaging (HSI) has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 21 publications
0
28
0
1
Order By: Relevance
“…One of the key issues involving optical analysis of fingerprints is to ensure sufficient ridge detail is captured to allow for comparison of crime scene marks against fingerprints from a suspect. The first part of this study [9] investigated the novel use of hyperspectral imaging for the analysis of blood stained fingerprints on white tiles. The main focus was to establish if ridge detail of a sufficient resolution could be determined, to potentially allow for fingerprint comparison.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key issues involving optical analysis of fingerprints is to ensure sufficient ridge detail is captured to allow for comparison of crime scene marks against fingerprints from a suspect. The first part of this study [9] investigated the novel use of hyperspectral imaging for the analysis of blood stained fingerprints on white tiles. The main focus was to establish if ridge detail of a sufficient resolution could be determined, to potentially allow for fingerprint comparison.…”
Section: Introductionmentioning
confidence: 99%
“…The approach carried out by our research group indicated a higher sensitivity and specificity for the detection and identification of blood stains over previously proposed methods [3]. Recent research has since successfully demonstrated the application of this technique for the detection, identification, and visualisation of ridge detail in blood stained fingerprints deposited on white ceramic tiles [19] and a range of other substrates commonly encountered at scenes of crime [20]. To date there has been no comparison between HSI and existing chemical enhancement methods, such as Acid Black.…”
Section: Introductionmentioning
confidence: 75%
“…The HSI system used in this study was the same setup detailed in [3] and [19,20], consisting of a liquid crystal tuneable filter (LCTF) coupled to a 2.3 megapixel Point Grey camera and a light source for scene illumination. The light source was comprised of two 40W LEDs; one violet giving an output at 410nm and one white giving an output between 450 and 700 nm.…”
Section: The Hyperspectral Imaging (Hsi) Systemmentioning
confidence: 99%
See 2 more Smart Citations